2012
DOI: 10.1093/cercor/bhs197
|View full text |Cite
|
Sign up to set email alerts
|

Regional Infant Brain Development: An MRI-Based Morphometric Analysis in 3 to 13 Month Olds

Abstract: Elucidation of infant brain development is a critically important goal given the enduring impact of these early processes on various domains including later cognition and language. Although infants' whole-brain growth rates have long been available, regional growth rates have not been reported systematically. Accordingly, relatively less is known about the dynamics and organization of typically developing infant brains. Here we report global and regional volumetric growth of cerebrum, cerebellum, and brainstem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 92 publications
4
54
1
4
Order By: Relevance
“…31 A more recent study that focused on infants (3-13 months of age) also observed an increasing volume of all gray matter regions with some regionally different growth patterns. 32 While volume increased, the ADC of the gray matter declined rapidly, with a fast exponential component in the first few years, which then stabilized in early adolescence. These findings likely reflect the combined effects of neuronal development, myelination, and decrease in water content 33 and associated MR imaging signal changes 34,35 that rapidly occur in the early years of development.…”
Section: Discussionmentioning
confidence: 99%
“…31 A more recent study that focused on infants (3-13 months of age) also observed an increasing volume of all gray matter regions with some regionally different growth patterns. 32 While volume increased, the ADC of the gray matter declined rapidly, with a fast exponential component in the first few years, which then stabilized in early adolescence. These findings likely reflect the combined effects of neuronal development, myelination, and decrease in water content 33 and associated MR imaging signal changes 34,35 that rapidly occur in the early years of development.…”
Section: Discussionmentioning
confidence: 99%
“…Choe et al (2013) llevaron a cabo un estudio sobre el crecimiento regional del cerebro a partir de un análisis morfométrico (volúmenes globales y locales) entre 3 y 13 meses.…”
Section: Maduración Cerebral Típica En Los Primeros Años De Vidaunclassified
“…En el hipocampo, se observó una asimetría hacia la derecha, que también ha sido documentada en otros estudios de niños recién nacidos prematuros y en los nacidos a término (Thompson et al, 2009), en niños mayores y adolescentes (Giedd et al, 1996;Pfluger et al, 1989) y en adultos (Jack et al, 1989;Li, Ga, Huo, Li, & Gao, 2007;Ystad et al, 2009). En este estudio, Choe et al (2013) también encontraron una consistente asimetría del hipocampo hacia la derecha, dato que sugiere que la dominación hippocampal derecha está presente en el nacimiento y persiste a través de la edad. El hipocampo derecho es crítico para la formación de la memoria episódica y espacial (Burgess, Maguire & O'Keefe, 2002).…”
Section: Maduración Cerebral Típica En Los Primeros Años De Vidaunclassified
See 2 more Smart Citations